Procedure Writing Methods in Library with Reference to ISO Standards 9001: 2008 - S, Maidhili; G, Meenambika (International Journal of Information Studies, 2025)
This paper gives a brief introduction about the steps of ISO implementation procedure writing on the different works of the library and to determine the performance of the services of the engineering college libraries. The main objectives of the college library have been improved for the implantation process. Different procedures have been written for the work execution and the performance of the service has been improved on the basis of the Standards of ISO.